Pengaruh ESG dan NPL terhadap Stock Return dengan Moderasi Covid-19 dan LDR pada Bank ASEAN - Anita; Erni Herniwati; Ahmad Fikri Alamin; Dwinjayana Santo Nugroho (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) and Non-Performing Loans (NPL) on stock returns in banking companies across ASEAN countries, as well as to examine the moderating roles of the Loan to Deposit Ratio (LDR) and the Covid-19 pandemic. A causal quantitative approach was employed, using secondary data from 98 banking firms listed in the ESG index from 2021 to 2023. Data analysis was conducted through multiple linear regression using SPSS version 25. The results indicate that ESG has a positive effect on stock returns, while NPL does not significantly affect stock returns. When moderated by LDR, ESG's effect becomes insignificant, whereas NPL shows a significant impact on stock returns. In contrast, moderation by Covid-19 does not significantly influence the relationship between ESG or NPL and stock returns.